2018
DOI: 10.1029/2018gh000146
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Phthalate Metabolites in Common Bottlenose Dolphins (Tursiops truncatus) From Sarasota Bay, FL, USA

Abstract: Phthalates are chemical additives to common consumer goods including cleaning products, cosmetics, personal care products, and plastic. Because they are not chemically bound to these products and are widely used, the potential for environmental contamination is significant. Phthalates and their metabolites have been associated with endocrine disruption and reproductive impairment, among other adverse health effects, in laboratory animals and human epidemiologic studies. Common bottlenose dolphins (Tursiops tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 69 publications
3
39
1
Order By: Relevance
“…This study relied upon bottlenose dolphin urinary metabolite concentrations reported in Hart et al [ 30 ] (sample years 2016–2017), as well as results from analyses conducted on samples collected 2010–2015 and 2018–2019. Urine samples were opportunistically collected aseptically via catheterization from bottlenose dolphins during routine health assessments conducted under permit from the National Oceanic and Atmospheric Administration’s (NOAA) National Marine Fisheries Service (NMFS) between 2010 and 2019, as described in Wells [ 42 ] and Hart et al [ 30 ]. Archived urine samples for the years 2010–2015 were retrieved from the Sarasota Dolphin Research Program’s specimen bank, where urine samples were stored frozen at -80°C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study relied upon bottlenose dolphin urinary metabolite concentrations reported in Hart et al [ 30 ] (sample years 2016–2017), as well as results from analyses conducted on samples collected 2010–2015 and 2018–2019. Urine samples were opportunistically collected aseptically via catheterization from bottlenose dolphins during routine health assessments conducted under permit from the National Oceanic and Atmospheric Administration’s (NOAA) National Marine Fisheries Service (NMFS) between 2010 and 2019, as described in Wells [ 42 ] and Hart et al [ 30 ]. Archived urine samples for the years 2010–2015 were retrieved from the Sarasota Dolphin Research Program’s specimen bank, where urine samples were stored frozen at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Archived urine samples for the years 2010–2015 were retrieved from the Sarasota Dolphin Research Program’s specimen bank, where urine samples were stored frozen at -80°C. The protocol for sample collection and storage for years 2016–2019 are described in Hart et al [ 30 ]. All urine samples were screened for eight phthalate metabolites including: monomethyl phthalate (MMP), monoethyl phthalate (MEP), monoisobutyl phthalate (MiBP), monobutyl phthalate (MBP), monobenzyl phthalate (MBzP), mono-(2-ethylhexyl) phthalate (MEHP), mono-(2-ethyl-5-oxohexyl) phthalate (MEOHP), and mono-(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations